Functional expression of Vanda Mimi Palmer monoterpene synthases in Pichia pastoris, a yeast system - Rahim Mohd-Hairul, Ab (2017)
There are more than 100 orchid species and hybrids that have been reported to emit fragrance compounds including monoterpenoids, sesquiterpenoids, benzenoids and phenylpropanoids, which have potential to be commercialized in the fragrance, flavour and food industries. Unfortunately, the price of scented orchids is too expensive and the supply of scented orchids is insufficient for essential oil extraction due to the infrequent flowering throughout the year. This study aims to isolate monoterpene synthase transcripts from selected orchids for overexpression in selected microbial systems via in vivo biosynthesis to fulfill the demand of monoterpene compounds by the fragrance, flavor and food industries. Transcriptomic sequencing on four selected scented orchids including Vanda Mimi Palmer, Vanda Small Boy Leong, Vanda Johanna Ljunggren and Vandachostylist Sri-Siam in comparison to a non-scented orchid Vanda Tan Chay Yan was chosen to identify monoterpene synthase transcripts responsible for the biosynthesis of monoterpene compounds. Open reading frames of four monoterpene synthases including linalool and ocimene synthases have been isolated and successfully transformed in selected microbial systems including Escherichia coli, Lactococcus lactis, Pichia pastoris and Kluvyromyces lactis. Functional expression of all linalool and ocimene synthases isolated from the orchids were carried out by recombinant protein analysis using SDS-PAGE and Western blot while fragrance compounds produced by the recombinant systems were analysed using Gas Chromatography-Mass Spectrometry. The targeted monoterpene products from the recombinant systems will be beneficial for large scale supplies of monoterpenoids to the fragrance, flavour and food industries.